TEKNOLOGI PENGOLAHAN JAMUR TIRAM DAN ANALISA USAHATANINYA DALAM MENDUKUNG AGROINDUSTRI - Sudarwati, Sri (Jurnal Ilmu-Ilmu Pertanian, 2019)
Oyster mushroom is one of the horticultural commodities that has high economic value and is very popular by the community because it is beneficial for bodily health. Content of oyster mushroom typical chemical compounds efficacious treat various human diseases such as high blood pressure, diabetes, excess cholesterol, anaemia, increase the bodys resistance to polio and influenzas attacks and nutritional deficiencies. Viewed from the health aspect, oyster mushrooms are nutritious food ingredients with medicinal properties which are cheaper than modern medicine. Oyster mushrooms are perishable food, where the damage can be caused by microorganisms, biochemical reactions (enzymatic browning) and chemicals (non-enzymatic browning) and physical damage. Therefore, after harvesting, it is consumed immediately or processed into various types of side dishes or snacks such as nuggets, chips and others. The implementation phase of this research is the making of nuggets, making chips, organoleptic tests and farming analysis. In making nuggets with two treatments, namely with boiled and not boiled mushrooms, while in making chips is the use of a mixture of wheat flour and rice flour and tapioca flour. The results of the study showed that in making nuggets both flavour, taste and texture are preferably boiled mushrooms, while the colours of boiled and not boiled mushrooms are equally preferred. In making chips, colour and texture are preferred by using a mixture of rice-tapioca lour, while the flavour and taste are equally preferred. From the results of farming analysis, the making of nugget and oyster mushroom chips is beneficial with the B / C ratio of 1.65 and 1.84, respectively. With the diversification of oyster mushroom preparations and profitable farming analysis results can support the creation or development of agroindustry.